The cost effectiveness of payments for ecosystem services—Smallholders and agroforestry in Africa. (February 2018) - Benjamin, Emmanuel O.; Sauer, Johannes
Highlights: Evaluate farm-level interaction between agriculture output and ecosystem services. Flexible transformation function is use to model the farm-level interactions. Joint agriculture output and ecosystem services production is mostly complementary. Abstract: Certain smallholder farmers in parts of sub-Saharan Africa engage in conservation agriculture and participate in agroforestry ecosystem services schemes that generate additional on-farm revenues through payment for ecosystem services (PES). However, smallholder farmers that are inadequately compensated for the foregone income from agricultural production due to marginal ecosystem services provision have no incentive to participate. On the other hand, over-compensating participating farmers will also lead to PES schemes inefficiencies. Therefore, stakeholders are confronted with the challenge of evaluating farm-level interactions between agricultural production and ecosystem services' provision when making strategic decisions on the efficient level of compensation. We propose in this contribution to assess the efficiency of PES schemes by measuring the marginal cost of ecosystem services based on farm level bio-economic interactions. The quantitative assessment is based on a theoretical classification of the relationship between marketed agricultural output and ecosystem services into complementary, supplementary or competitive. We use a flexible transformation function and cross-sectional data on 120 surveyed smallholder farmers with agroforestry certification in rural Mount Kenya. The results suggest that the joint production (of agricultural output and ecosystem services) for a substantial number of smallholder farms in Kenya may not show a complementary relationship. The biophysical linkage between marketed outputs and ecosystem services strongly influences the marginal cost of ecosystem services. PES schemes could become more efficient if they would target smallholder farms based on the aforementioned classifications by offering a range of contracts to encourage competitive bidding.